Does Foot Massage Relieve Acute Postoperative Pain? A Literature Review - Chanif, Chanif; Petpichetchian, Wongchan; Chongchareon, Wimonrat (Nurse Media Journal of Nursing, 2013)
Purpose: This study aimed to examine the current state of knowledge regarding foot massageto determine if foot massage has an effect on relieving acute postoperative pain.Method: The following questions were used to guide this review: How does pain occur?What is the pain management modalities used in relieving acute postoperative pain? Does footmassage relieve acute postoperative pain? A comprehensive systematic search of publishedliterature and journal articles from Science Direct, CINAHL, PubMed, ProQuest and fromrelevant textbooks was conducted. The universal case entry website, Google-scholar was usedas well. The following keywords were used: foot massage, pain management, andpostoperative pain. Eight studies on foot massage and more than thirty related articles werereviewed.Result: Postoperative pain is caused by tissue damage that induces release of chemicalmediators from the surgical wound. The four processes of pain are transduction, transmission,perception and modulation. Pain medication is the goal standard for acute postoperative painrelief. In addition, foot massage is a modality that can be used in relieving acute postoperativepain. Massage stimulates large nerve fibers and dermatome layers which contain tactile andpressure receptors. The receptors subsequently transmit the nerve impulse to the centralnervous system. The gate control system in the dorsal horn is activated through the inhibitoryinterneuron, thus closing the gate. Subsequently, the brain does not receive the pain message.Eight reviewed studies demonstrated that foot massage relieves acute postoperative pain.However, there were some methodological limitations of these studies.Conclusion: It is recommended to examine the effect of foot massage on acute postoperativepain with high homogenous samples using various duration of massage and range of time forpain measurement at different settings.Key words: foot massage, pain management and postoperative pain.